Hypovitaminosis D In Chronic Low Back Pain - Attiya Istarini (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Vitamin D deficiency has been linked to various pain conditions, including chronic low back pain. The role of vitamin D for the health of the musculoskeletal system involves the downregulation of pro-inflammatory cytokines that contribute to pain and the upregulation of anti-inflammatory cytokines that help reduce inflammation. Hypovitaminosis D can result from various factors, including age, low exposure to sunlight, dietary factors and genetic. Objectives: This study aimed to determine vitamin D levels in chronic low back pain patients. Methods: This research is an observational study with a cross sectional design. The population was all patients with chronic low back pain for more than 3 months. All samples underwent a total Vitamin D 25-OH examination using the Enzyme Linked Fluorescent Assay (ELFA). Results: This study found that the majority of participants are elderly women (73.5%) aged 56-65 years (30.6%). In this study 59.2% of participants had vitamin D deficiency and 30.6% had vitamin D insufficiency. Based on radiological examination, 34.7% had lumbar osteoarthritis. Conclusion: Patient with chronic low back pain had low level of vitamin D. Adequate sunlight exposure, dietary intake, and supplementation when necessary are essential strategies to prevent vitamin D deficiency and its associated health risks in the aging population. Key words: Chronic low back pain, Vitamin D